miR-19a-3p affected ox-LDL-induced SDC-1/TGF-β1/Smad3 pathway in atherosclerosis: miR-19a-3p inhibited SDC-1/TGF-β1/Smad3 - Jin, Qiao; Deng, Yiming; Li, Liang; Chen, Ran; Jiang, Luping (Cellular and Molecular Biology, 2023)
Syndecan-1 (SDC-1) was a critical membrane proteoglycan and an important component of the glycocalyx in endothelial cells, but its role in atherosclerosis remains unknown. This study attempted to investigate the role of SDC-1 in atherosclerotic-related endothelial cell injury. Bioinformatics analyzed the differential miRNAs between atherosclerosis and healthy. Subjects with coronary atherosclerosis, which were diagnosed with intravascular atherosclerosis (IVUS), were enrolled as non-vulnerable plaque and vulnerable plaque in Changsha Central Hospital. Human aortic endothelial cells (HAECs) were induced by oxidized low-density lipoprotein (ox-LDL) to construct an in vitro model. A dual luciferase reporter assay was applied to analyze the target between miR-19a-3p and SDC-1. The cell proliferation and apoptosis were detected by CCK8 and flow cytometry, respectively. SDC-1 and cholesterol efflux was determined by ELISA. The expression of ATP-binding cassette (ABC) transports A1 (ABCA1), miR-19a-3p, ABCG1 and SDC-1 genes were detected by RT-qPCR. The expressions of SDC-1, ABCA1, ABCG1, TGF-β1, Smad3 and p-Smad3 proteins were detected by western blot. Our results found that miR-19a-3p was down-regulated in atherosclerosis. ox-LDL decreased miR-19a-3p expression, increased cholesterol efflux and the expression of ABCA1, ABCG1 and SDC-1 in HAECs. Vulnerable plaque tissues in patients with coronary atherosclerosis showed palpable fibrous necrosis and calcification with elevated blood SDC-1 levels. miR-19a-3p could bind to SDC-1. Overexpression of miR-19a-3p promoted cell proliferation, inhibited apoptosis and cholesterol efflux, down-regulated the expression of SDC-1, ABCA1, ABCG1, TGF-β1 and p-Smad3 proteins in ox-LDL-induced HAECs. In conclusion, miR-19a-3p targeting SDC-1 inhibited the ox-LDL-induced activation of the TGF-β1/Smad3 pathway in HAECs.